Modelowanie warunków świetlnych na dnie lasu - Bolibok, Leszek; Brach, Michał; Drozdowski, Stanisław; Orzechowski, Michał (Leśne Prace Badawcze, 2013)
Contemporary models of light conditions on the forest floor can be divided into two categories: undercanopy models that allow the light conditions in a stand under the canopy to be simulated, and models that take into account shielding from the side. Under-canopy models precisely estimate the availability of wavelengths of light spatially distributed under the canopy of stands: however these models require a large amount of data on the spatial structure of forest stands. The other class of models describes the light conditions on a particular open surface. These incorporate shielding from the side and are easier to use as they require less data than under-canopy models. In practice, in forest conditions, such models require data on the size, shape, and geographical location of surveyed surfaces (e.g. gaps, and cut areas) and on the height of the surrounding stand. Often, these data are available in databases, such as the State Forest Information System (SILP), can otherwise be obtained relatively easily (and inexpensively). Compared to under-canopy models, these models provide a cheap way to obtain useful information on variation in the light environment that affects the microclimate for regenerating plants on clearcuts and canopy gaps.